Frommer's Paris 2007 - Porter, Darwin (NC, 2006)
1 online resource (viii, 340 pages) : | Frommer's. The best trips start here. Experience a place the way the locals do. Enjoy the best it has to offer. Ways to explore the City of Light from the top of La Tour Eiffel to the infamous catacombs. Outspoken opinions on what's worth your time and what's not | Includes bibliographical references and index | Print version record | Frommer's Paris 2007; Contents; List of...
Droits a verifier sur la notice Internet Archive
Keywords: Tour Eiffel